Complications of the subcutaneous route in the infusion of medications and solutions in palliative care - Natália de Almeida Barbosa Guedes; Laís Samara de Melo; Fernanda Batista Oliveira Santos; Jaqueline Almeida Guimarães Barbosa (Rev Rene, 2019)
Objective: to characterize the complications associated with the use of the subcutaneous route for infusion of drugs and solutions in palliative care. Methods: observational, prospective study conducted at the Palliative Care Unit of a general teaching hospital. Results: the study analized seventy-eight patients in palliative care, in whom 254 punctures for infusion of drugs and/or solutions through the subcutaneous route were made. Most patients were elderly (87.3%) and malnourished (69.2%). In 33.0%, the route was indicated for symptom control; in 50.0%, the puncture occurred in the anterolateral thigh flap; 65.4% of the punctures showed no complication. Among the identified complications, 9.4% were edema and 9.1% hyperemia, and 53.8% occurred in the deltoid region. Cellulite occurred in only 3.5%. Conclusion: the infusion of solutions using the subcutaneous route can be considered a safe alternative, with risk of complications which are mostly reversible and with low potential to cause damage to patients.